Development of left ventricular hypertrophy in a novel porcine model of mitral regurgitation*. (June 2014) - Ravn, Nathja; Zois, Nora E.; Moesgaard, Sophia G.; Honge, Jesper L.; Smerup, Morten H.; Hasenkam, J. Michael; Sloth, Erik; Cremer, Signe E.; Olsen, Lisbeth H.
Abstract Objectives. We aimed to develop a porcine model for chronic nonischemic mitral regurgitation (MR) to investigate left ventricular (LV) enlargement and eccentric hypertrophy. Design. Nonischemic MR was induced in 30 pigs by open-chest immobilization of the posterior mitral leaflet by transannular traction sutures that where applied in transmyocardial fashion. A sham operated control group (n = 13) was included. Echocardiographic LV size and heart weight assessed at euthanasia were used to evaluate the development of LV enlargement and eccentric hypertrophy after 8 weeks follow-up. Results. Eight pigs died and seven were excluded due to mediastinal infection (n = 2) or failure to produce MR (n = 5). Thus, 28 pigs were included and were divided into three groups: controls (n = 12), mild MR (mMR; n = 10), and moderate to severe MR (sMR; n = 6). The change in LV internal diameter in diastole (LVIDd) from baseline to follow-up was significantly higher in the sMR group compared to that of the control group (P = 0.0017). Furthermore, LV weight was significantly increased in the mMR (P = 0.047) and the sMR (P = 0.0087) groups compared to that of the control group. Conclusions. A new model for chronic moderate to severe nonischemic MR with development of LV enlargement and eccentric hypertrophy within 8 weeks has been established in pigs.